Inflation expectations and behavior: Do survey respondents act on their beliefs? - Olivier Armantier; Wändi Bruine de Bruin; Giorgio Topa; Wilbert van der Klaauw; Basit Zafar (Federal Reserve Bank of New York, 2011)
We compare the inflation expectations reported by consumers in a survey with their behavior in a financially incentivized investment experiment designed such that future inflation affects payoffs. The inflation expectations survey is found to be informative in the sense that the beliefs reported by the respondents are correlated with their choices in the experiment. Furthermore, most respondents appear to act on their inflation expectations showing patterns consistent (both in direction and magnitude) with expected utility theory. Respondents whose behavior cannot be rationalized tend to be less educated and to score lower on a numeracy and financial literacy scale. These findings are therefore the first to provide support to the microfoundations of modern macroeconomic models.
Keywords: C83; D12; E60; C90; 330; inflation expectations; surveys; experimental economics